2009
DOI: 10.2147/vhrm.s5639
|View full text |Cite
|
Sign up to set email alerts
|

Anteroposterior diameter of the infrarenal abdominal aorta is higher in women with polycystic ovary syndrome

Abstract: Background: Women affected by polycystic ovary syndrome (PCOS) are known to be at higher risk of cardiovascular disease. The aim of this study was to identify the artery that first is affected by early pre-atherosclerotic changes in PCOS. Methods: Twenty-nine women with PCOS aged 17 to 27 years and 26 healthy nonhyperandrogenic volunteers with regular menses (control women) aged 16 to 28 years were enrolled. All PCOS patients were overweight or obese (body mass index [BMI]  25). Diagnosis of PCOS was performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…Our observations are in agreement with previous findings in adolescents with PCOS [53][54][55][56]. High IMT values in PCOS were reported in women in early adulthood (associated with decreased sex hormone-binding globulin) [57] and adulthood [58][59][60][61][62][63][64][65] in obese women [50,66,67] and patients with juvenile rheumatoid arthritis [68]. Our study participants were adolescent and young adult women with PCOS and proper controls matched for BMI, so as to overcome the strong confounding associations of age and BMI with arterial thickness in PCOS [68].…”
Section: Commentsupporting
confidence: 92%
“…Our observations are in agreement with previous findings in adolescents with PCOS [53][54][55][56]. High IMT values in PCOS were reported in women in early adulthood (associated with decreased sex hormone-binding globulin) [57] and adulthood [58][59][60][61][62][63][64][65] in obese women [50,66,67] and patients with juvenile rheumatoid arthritis [68]. Our study participants were adolescent and young adult women with PCOS and proper controls matched for BMI, so as to overcome the strong confounding associations of age and BMI with arterial thickness in PCOS [68].…”
Section: Commentsupporting
confidence: 92%
“…All these results confirm several studies showing that young PCOS women have an adverse cardiovascular risk profile, and a higher cardiovascular risk [ 19 , 20 ]. Previous studies had clearly shown an association between PCOS and carotid intima-media thickness [ 21 ] or anteroposterior diameter of infrarenal abdominal aorta [ 22 ]. Moreover, other studies had shown a correlation between PCOS and serum markers of atherosclerosis such as CRP [ 23 ], interleukin-18 [ 24 ], homocysteine [ 25 ], and endothelial dysfunction [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…There was no common iliac artery corresponding to that of humans, which arises from the aorta and branches off into the external and internal iliac arteries. Although differences in vascular diameter, morphology, and branching pattern between micropigs and human [ 2 , 19 , 25 , 30 , 39 ] can be overcome with modern surgical techniques at the time of transplantation, there is the possibility that the function of the related micropig organs could be compromised in human systems following transplantation. Thus, further studies are needed to evaluate and compare micropig organ function with that of humans.…”
Section: Discussionmentioning
confidence: 99%